Экспериментальные исследования процесса копания грунтов роторно-дисковыми рабочими органами под гидростатическим давлением - Rakhimzhan Abylkasymovich Kabashev; Sanzharbek Jenishbekovich Turgumbaev (Вестник СибАДИ, 2017)
As a result of experimental studies the obtained regularities of influence of hydrostatic pressure on the process of soil digging knives of a rotary disk of the working body. It is found that for cohesive soils, the resistance to digging of the soil by the knives of a rotary disk of the working body increases with increasing values of the hydrostatic pressure (the depth of immersion of the working body). The design of stand of physical modeling to study the process of soil digging knives of a rotary disk of the working body under hydrostatic pressure. The depth of immersion of the working body in a liquid was simulated by the creation of a corresponding hydrostatic pressure in the hermetic housing of the stand. Based on strain records obtained values of the tangential component of the effort of digging the soil and values of traction resistance of digging trenches under hydrostatic pressure.